Metagenomic quorum quenching enzymes affect biofilm formation of Candida albicans and Staphylococcus epidermidis. - Nancy Weiland-Bräuer; Irene Malek; Ruth A Schmitz (PLoS ONE, 2019)
Biofilm formation in the clinical environment is of increasing concern since a significant part of human infections is associated, and caused by biofilm establishment of (opportunistic) pathogens, for instance Candida albicans and Staphylococcus epidermidis. The rapidly increasing number of antibiotic-resistant biofilms urgently requires the development of novel and effective strategies to prevent biofilm formation ideally targeting a wide range of infectious microorganisms. Both, synthesis of extracellular polymeric substances and quorum sensing are crucial for biofilm formation, and thus potential attractive targets to combat undesirable biofilms.We evaluated the ability of numerous recently identified metagenome-derived bacterial quorum quenching (QQ) proteins to inhibit biofilm formation of C. albicans and S. epidermidis. Here, proteins QQ-5 and QQ-7 interfered with the morphogenesis of C. albicans by inhibiting the yeast-to-hyphae transition, ultimately leading to impaired biofilm formation. Moreover, QQ5 and QQ-7 inhibited biofilm formation of S. epidermidis; in case of QQ7 most likely due to induced expression of the icaR gene encoding the repressor for polysaccharide intercellular adhesin (PIA) synthesis, the main determinant for staphylococcal biofilm formation. Our results indicate that QQ-5 and QQ-7 are attractive potential anti-biofilm agents in the prevention and treatment of C. albicans and S. epidermidis mono-species biofilms, and potentially promising anti-biofilm drugs in also combating multi-species infections.